Elaborações de estudantes do 7° ano do ensino fundamental sobre números inteiros e suas operações - Silva, Maristela Alves (2012)
This research is qualitative and has as main objective to analyze the main elaborations explained by students from 7th year of elementary school on integers and its operations. Students were enrolled in a public school in the city of Fernandópolis - SP. The question that guides the study is: What elaborations students manifest and / or explicit experience while guiding the activities of teaching with integers? The route goes through the history of this work of integers, number theory, and curriculum of the State of São Paulo, including therein, the experience of the students with the concepts studied, from Guiding Teaching Activities. The activities were prepared by the teacher of the class, and initially considered the learning situations proposed by books, the Department of Education of the State of São Paulo. During their development was necessary to make adjustments so that students can understand the concepts studied. These adjustments were made, fed back from the students as well as the reflections of the teacher. The focus of the research is the process and not just the result obtained by students after solving activities. The elaborations of the students are explained through dialogues that occur during the experience of the activities in the classroom. Students explicit oral that: a) believe that below zero there is no number, b) the minus sign is meaningless and c) it is impossible to operate negative quantities. The activities are aimed at questioning and questioning the "truths" momentary explained by students, providing moments in which to formulate new ideas, based on the needs required activities.